The Role of Kersik Tuo Village Government in Sustainable Tourism Development in Mount Kerinci Hiking Trail - Ikhfal Halmaf Kholif; Ika Devi Pramudiana; Sri Kamariyah; Feri Ramadhan (International Journal of Social Welfare and Family Law, 2025)
Mount Kerinci is one of Indonesia’s premier climbing tourist destinations, attracting a growing number of visitors each year. This rapid increase in tourism has brought about significant ecological and social pressures on the surrounding environment and communities. Kersik Tuo Village, serving as the primary gateway to the hiking trail, holds a pivotal role in managing these pressures through sustainable tourism practices. This study aims to analyze the role of the Kersik Tuo Village Government in advancing sustainable tourism development using a qualitative descriptive approach, guided by William N. Dunn's program evaluation framework. The framework assesses five key criteria: effectiveness, efficiency, adequacy, equity, and responsiveness. Findings indicate that the village government has implemented several important initiatives, such as developing basic infrastructure, conducting human resource training, running environmental awareness campaigns, and collaborating with the village-owned enterprise (BUMDes) to boost local economic development. Despite these positive steps, significant challenges persist. Waste accumulation above 3,000 meters remains a critical environmental concern, alongside widespread illegal climbing activities that threaten the conservation area. Economic benefits are unevenly distributed among community members, and village officials face limitations in technical capacity, hindering effective management. While the government shows good responsiveness to environmental issues, its efforts fall short in addressing social conflicts and systematic trail monitoring. To address these gaps, the study recommends strengthening institutional frameworks, enhancing coordination among all tourism stakeholders, establishing preventive monitoring systems for trails, and promoting inclusive economic empowerment. These combined efforts are essential to foster equitable, participatory, and sustainable governance for climbing tourism within the Mount Kerinci conservation area, ensuring long-term preservation and community welfare.